The Evidentiary Crisis in Criminal Defamation in the Digital Space: Between Public Perception and Legal Truth - Friska Anggi Siregar; Nur Sari Dewi M; Muslem Ibnu (FASYA Press, 2026)
This study aims to analyse the evidentiary crisis in the crime of defamation in the digital space and examine how the interaction between legal norms, electronic evidence, and public perception affects the determination of legal truth. This study uses normative legal research combined with a socio-legal perspective. The results of the study show that the digital evidence crisis is influenced by four main factors, namely the ambiguity of legal norms that opens up space for subjective interpretation, the instability of digital evidence that is vulnerable to manipulation, the dominance of public perception that forms social legitimacy before the formal adjudication process, and the increasing influence of digital platforms in the distribution of information and the formation of public perception. The findings of the study show that the evidentiary process in the digital era is no longer fully determined by formal legal verification mechanisms, but is also influenced by the dynamics of digital communication, information virality, and social construction in the digital space. This research develops the concept of